Corporate Policies and Practices among Contingent Workers in Private Retail Stores: Basis for Intervention Measures - Rachel Ann Q. Capacite; Jeffrey G. Capacite (East Asian Journal of Multidisciplinary Research, 2023)
This study explores the complex landscape of business policies and practices relating to contingent labor in the setting of independent retail stores. The workforce in the retail sector is largely made up of contingent workers, who frequently include temporary, part-time, seasonal, and contract employees. Due to the needs of contemporary techniques like just-in-time production as well as seasonal and cyclical dynamics, contingent contracts enable some businesses to maximize employee flexibility. They regrettably frequently earn less money and receive less benefits than regular full-time or "permanent" employees, and they are less likely to be covered by labor and employment regulations. This study utilized the descriptive method of research (Walpole, 2023). As widely accepted, the descriptive method of research is a fact-finding study that involves adequate and accurate interpretation of findings. The purpose of this study is to affirm contingent workers’ valuable role in diversifying the forms of employment relationships available to meet the needs of companies and workers following the corporate policy and practices and what intervention measures will be used to have a smooth operational flow within a company.